AN ANALYSIS OF THE EXPRESSIVE SPEECH ACTS IN “AVATAR: WAY OF THE WATER” MOVIE - Roby Octo Aritonang Aritonang; Ambalegin Ambalegin (IdeBahasa, 2023)
This research focused on investigating the expressive speech acts found in “Avatar: The Way of The Water” Movie. The research implied the theory of Searle and Vanderveken (1985). In collecting the data, the method is observation, and the technique is note-taking. In analyzing the data, the data were examined using the pragmatic identity method and pragmatic competence-in-equalizing technique. The data was taken from the utterances in the Avatar movie. There are 46 expressive speech acts found in the movie which are divided into 10 acts. The expressive speech acts with most occurrences were complaint with 11 occurrences, followed by 8 data of greet, 7 data of apologize, 5 data of compliment, 5 data of protest, 3 data of lament, 3 data of thank, 2 data of boast, 1 data of praise, and 1 data of deplore. The expressive speech acts condole and congratulate were not found in the movie, because the death mostly was found in the war and the victory achieved was an obligation that they had to do.